2014
DOI: 10.1063/1.4872060
|View full text |Cite
|
Sign up to set email alerts
|

Strongly enhanced vortex pinning from 4 to 77 K in magnetic fields up to 31 T in 15 mol.% Zr-added (Gd, Y)-Ba-Cu-O superconducting tapes

Abstract: Applications of REBCO coated conductors are now being developed for a very wide range of temperatures and magnetic fields and it is not yet clear whether vortex pinning strategies aimed for high temperature, low field operation are equally valid at lower temperatures and higher fields. A detailed characterization of the superconducting properties of a 15 mol. % Zr-added REBCO thin film made by metal organic chemical vapor deposition, from 4.2 to 77 K under magnetic fields up to 31 T is presented in this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
116
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 39 publications
19
116
0
1
Order By: Relevance
“…It is expected that the engineering current density of the tapes will still increase significantly. On short lengths very high current densities have already been achieved using Zr doping [11], [12]. When such conductors become available in longer lengths one can imagine an efficient, low cross sectional area, very high field magnet.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the engineering current density of the tapes will still increase significantly. On short lengths very high current densities have already been achieved using Zr doping [11], [12]. When such conductors become available in longer lengths one can imagine an efficient, low cross sectional area, very high field magnet.…”
Section: Introductionmentioning
confidence: 99%
“…3,16 Moreover, recent work has shown that large quantities (⩾10%) of second-phase additions are required to obtain the desired level of performance in superconductors. [17][18][19] Until now, such a large amount of second phase resulted in current blocking and the loss of crystallinity. 19,20 For REBCO superconductors, MOD has been shown to be amenable for growing extremely high performance materials [21][22][23][24][25][26] with high throughput; [27][28][29] however, the tailoring of NP inclusions is extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
“…This has turned out to be a highly non-trivial requirement, although great advances have been made recently in this direction. [1][2][3][4] It was discovered empirically that vortex pinning was in general much weaker in the HTS than in low temperature superconductors. It is well understood that the very short coherence length plays an important role in this difference.…”
mentioning
confidence: 99%
“…2 In addition to the strain effect, we believe that overdoping may also contribute to the record values of the irreversibility field recently reported for YBCO films including BZO inclusions. [1][2][3] A theory that explains how strain can induce vortex pinning can be based on the Bond Contraction Pairing (BCP) model. 18 This model predicts that a contraction of the order of 1% of Cu-O bonds is sufficient to induce pair localization.…”
mentioning
confidence: 99%